2019
DOI: 10.1186/s12984-019-0510-3
|View full text |Cite
|
Sign up to set email alerts
|

Does severity of motor impairment affect reactive adaptation and fall-risk in chronic stroke survivors?

Abstract: BackgroundA single-session of slip-perturbation training has shown to induce long-term fall risk reduction in older adults. Considering the spectrum of motor impairments and deficits in reactive balance after a cortical stroke, we aimed to determine if chronic stroke survivors could acquire and retain reactive adaptations to large slip-like perturbations and if these adaptations were dependent on severity of motor impairment.MethodsTwenty-six chronic stroke participants were categorized into high and low-funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 98 publications
(82 reference statements)
0
16
0
Order By: Relevance
“…Continuous perturbations of stance have positive effects in the rehabilitation of balance in ageing [126], patients with neurological or vestibular deficits [127], cerebellar disease [128], stroke [83], Parkinson´s disease [6]. Exercises based on head movement have been beneficial in patients with vestibulopathy [129].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous perturbations of stance have positive effects in the rehabilitation of balance in ageing [126], patients with neurological or vestibular deficits [127], cerebellar disease [128], stroke [83], Parkinson´s disease [6]. Exercises based on head movement have been beneficial in patients with vestibulopathy [129].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we would suggest that the time course (but not the quality) of the adaptation process is partly set by the number of cycles and is based either or both on the sensory inputs originating during each cycle and on the anticipatory adjustments preceding the anterior and posterior dead points of each translating cycle. A broadly similar number of events has been counted in other balance adaptation studies [ 32 , 47 , 53 , 55 , 65 , 80 83 ], including events of perturbed gait ([ 84 ], for a recent review). The main process of adaptation would be relatively independent from the time elapsing from the beginning of the sequence of perturbation but be calibrated on the frequency of discrete changes in the direction of the AP platform translations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevisipour et al (38) reported that in people who have had a stroke, a training session of 15 posterior treadmill translation perturbations during stance resulted in reduced trunk flexion during recovery from a similar but untrained perturbation, indicating a training-related improvement, but trunk flexion velocity, reaction time, step duration, step length, and stability did not improve. Bhatt et al (39) applied repeated anterior surface translation perturbation (initiating backward balance loss) to stance in people who have had a stroke with both higher and lower motor impairment. Both groups improved in their ability to cope with the perturbations (fewer falls and better stability control), but there was a slower rate of adaptation over the trials in people with more severe motor impairment.…”
Section: Improving Trip-and Slip-resisting Skillsmentioning
confidence: 99%
“…[9][10][11][12][13] These measures are based on clinical characteristics of the patient and provide cumulative evaluations for the management of poststroke treatment care. Accurate predictions of ambulatory functions are needed as well, so that clinicians can help patients set motor recovery goals to improve activities of daily living [14][15][16][17][18] following thrombolysis therapy.…”
Section: Introductionmentioning
confidence: 99%